plz answer this guys
Attachments:
![](https://hi-static.z-dn.net/files/d7e/9a577cd620f70e1385209ad615b854d9.jpg)
Answers
Answered by
7
Answer:
2 a₆ - 3 a₄ = - 1
Step-by-step explanation:
Given----> aₙ = Cosⁿα + Sinⁿα
To find ----> Value of ( 2 a₆ - 3 a₄ )
Concept used ---->
1)
2)
3)
Solution-----> ATQ,
aₙ = Cosⁿα + Sinⁿα
a₆ = Cos⁶α + Sin⁶α
= ( Cos²α )³ + ( Sin²α )³
= ( Cos²α + Sin²α ) { ( Cos²α )² + ( Sin²α )² - Cos²α Sin²α }
= ( 1 ) { ( Cos²α )² + ( Sin²α )² + 2 Sin²α Cos²α - 3 Sin²α Cos²α }
= ( Cos²α + Sin²α )² - 3 Sin²α Cos²α
= ( 1 )² - 3 Sin²α Cos²α
= 1 - 3 Sin²α Cos²α
Now ,
a₄ = Cos⁴α + Sin⁴α
= ( Cos²α )² + ( Sin²α )² + 2 Sin²α Cos²α
- 2 Sin²α Cos²α
= ( Cos²α + Sin²α )² - 2 Sin²α Cos²α
= ( 1 )² - 2 Sin²α Cos²α
= 1 - 2 Sin²α Cos²α
Now, 2 a₆ - 3 a₄
Answered by
0
Attachments:
![](https://hi-static.z-dn.net/files/dde/256d088c2f96bed57813ee8274e3503d.jpg)
Similar questions
Hindi,
6 months ago
Environmental Sciences,
6 months ago
Math,
6 months ago
English,
1 year ago
English,
1 year ago
CBSE BOARD X,
1 year ago
Hindi,
1 year ago